ETHNOECOLOGICAL ESSENCE OF THE ANCIENT ECONOMIC SYSTEM (Scientific journal of the Fergana State University, 2025)
The article analyzes the ethnoecological nature of ancient agricultural systems. In particular, it examines the inseparable links between man and nature, the rational use of natural resources, and the influence of folk traditions on economic culture. It is emphasized that ancient economic systems played an important role not only in economic activity, but also in ensuring socio-ecological balance. The article analyzes the lifestyle, methods of nature management, and ecological principles of peoples based on ethnographic data and historical sources. It also emphasizes the importance of these systems in solving modern environmental problems.